Metal organic framework material composite membrane as well as preparation method and application thereof
By designing the structure of the substrate, hydrophilic layer, adsorption layer and fixed layer in the membrane material, and using carbide metal organic frame materials and hydrophilic polymers, the problems of difficult processing and complex film making process in traditional MOFs materials are solved, and efficient gas adsorption and enrichment effects are achieved.
Patent Information
- Application Number
- CN202411695207.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Traditional metal organic frame materials (MOFs) are difficult to handle, easily wear, and hinder fluid flow due to powder form. In addition, the existing film making methods have harsh reaction conditions, complex processes and high requirements for the film substrate, resulting in problems of stability and density of the film structure.
The metal organic frame material composite film structure is adopted, including a substrate, a hydrophilic layer, an adsorption layer and a fixed layer. The carbonized metal organic frame material is used as the adsorption layer and the hydrophilic polymer is used as the fixed layer. The hydrophilic layer improves the adsorption layer, and the fixed layer fixes the adsorption layer to form an efficient adsorption material.
It has achieved good adsorption performance, good mechanical properties, good stability and high density of the composite film. It has a simple preparation process and does not require complex processes such as pressurized molding. It is suitable for gas adsorption and enrichment, especially for krypton and xenon.
Smart Images

Figure CN119633770A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane materials, and in particular relates to a metal organic framework material composite membrane and a preparation method and application thereof. Background Art
[0002] Metal organic framework materials (MOFs) are materials with porous structures and high specific surface areas, and have good adsorption properties. However, traditional metal organic framework materials (MOFs) are usually synthesized in the form of crystalline powders, and the crystallite size ranges from nanometers to hundreds of micrometers. The powder form of MOFs materials greatly hinders their industrial application. There are problems such as: powders are difficult to handle, easy to wear, easy to hinder or reduce fluid flow, and powder purging during the preparation process easily causes the quality loss of MOFs powder. The current solution is to use adhesives to combine with MOFs powders, including polymer adhesives such as PVA, PVB, MC, etc. and inorganic adhesives such as ρ-alumina, silica, etc., and use pressurized or non-pressurized processes to make MOFs materials into small balls, particles, sheets or whole forms for use. This molding process has high requirements on the mechanical strength and stability of the material after molding, and there are problems such as large space occupation and cumbersome process operations in industrial production applications.
[0003] Membrane enrichment and separation technology is widely used in industrial production due to its simple operation, easy maintenance, low energy consumption and good separation effect. Among them, membrane enrichment and separation technology provides the possibility for the enrichment and treatment of radioactive gas-borne effluents in nuclear power plants and fuel reprocessing. For example, the α-ray penetration ability released by Kr-85 gas is weak. The use of thin film enrichment technology can not only solve the current problem of inaccurate trace gas monitoring, but also the design of the film does not affect the penetration of radioactive gas rays. Therefore, this technology can provide technical support for the detector to accurately monitor the effluent through the enrichment effect of trace inert gases, and also provide accurate data support for the environmental safety assessment of nuclear power plants. The preparation of the membrane is an important factor affecting the adsorption enrichment effect.
[0004] The existing membrane preparation methods mainly include microwave assisted thermal deposition, chemical vapor deposition technology, in-situ growth, secondary growth and layer-by-layer assembly, etc. These methods are mostly studied for the preparation of MOFs membrane materials. However, these technologies have relatively harsh reaction conditions, complex processes, and high requirements for membrane substrates. There are problems with the stability and density of the membrane structure. Summary of the invention
[0005] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a metal-organic framework material composite membrane, which has good adsorption performance, good mechanical properties, good stability, high density, and a simple preparation process without the need for complex processes such as press molding.
[0006] A second object of the present invention is to provide a method for preparing the above-mentioned metal organic framework material composite film.
[0007] The third object of the present invention is to provide an application of the metal organic framework material composite membrane or the metal organic framework material composite membrane prepared by the above preparation method in gas adsorption enrichment.
[0008] A fourth object of the present invention is to provide a method for enriching krypton and / or xenon by adsorption.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The first aspect of the present invention provides a metal organic framework material composite membrane, comprising a substrate, a hydrophilic layer, an adsorption layer and a fixed layer arranged in sequence; the fixed layer is coated on the surface of the adsorption layer and connected to the hydrophilic layer; the adsorption layer contains a carbonized metal organic framework material, and the fixed layer contains a hydrophilic polymer; the hydrophilic polymer includes at least one of gelatin, hyaluronic acid, chitosan, hyaluronic acid, polyethylene glycol, polyacrylic acid and its derivatives, polyvinyl alcohol, polyethylene oxide, polyacrylamide, polyhydroxyethyl methacrylate, polyacrylic acid or polymethacrylic acid.
[0011] The metal organic framework material composite film according to the first aspect of the present invention has at least the following beneficial effects:
[0012] In the present invention, a hydrophilic layer is firstly arranged on the surface of the substrate to improve the hydrophilicity and adhesion of the substrate surface, which is beneficial to the attachment of the subsequent adsorption layer and the fixed layer. Due to the arrangement of the hydrophilic layer, the composite membrane can adopt substrates with various properties, and the requirements for the membrane substrate are low; if the hydrophilic layer is not arranged, the adsorption layer and the fixed layer are difficult to be evenly dispersed and attached to the substrate, and the hydrophilic polymer of the fixed layer is also easy to agglomerate due to uneven distribution, resulting in uneven performance of the membrane material and poor material stability; then, carbonized metal organic framework materials (MOFs) are used as the adsorption layer. Carbonized MOFs have rich mesoporous structures and high specific surface areas. As adsorption materials It is beneficial to improve the adsorption activity of the composite membrane; and a fixed layer is set on the surface of the adsorption layer. Due to the good adhesion between the hydrophilic polymer in the fixed layer and the hydrophilic layer, the fixed layer plays a role similar to a "seat belt", wrapping the adsorption layer in contact with the hydrophilic layer, and better fixing the adsorption layer firmly in the membrane material to form a composite membrane material containing carbonized MOFs; and the hydrophilic polymers used in the present invention have good hydrophilic properties, strong adhesion to the hydrophilic layer, and good air permeability and stability, and will not affect the adsorption performance of the adsorption layer. While fixing the carbonized MOFs particles in the adsorption layer, it does not affect the adsorption activity of the carbonized MOFs. Through the design of the composite membrane structure of the present invention, a MOFs composite membrane with good adsorption performance is simply and efficiently prepared, without the need to adopt complex processes such as press molding, and the preparation process is simple. The obtained composite membrane has good mechanical properties, good stability, and high density, and has good application prospects in the preparation of gas adsorption materials.
[0013] In some specific embodiments of the present invention, the raw material for preparing the hydrophilic layer includes at least one of polyacrylic acid, methanol, ethanol or propanol.
[0014] In some specific embodiments of the present invention, the material of the substrate includes at least one of polyethylene terephthalate, a silicon plate, an aluminum foil or a plastic plate.
[0015] In some specific embodiments of the present invention, the mass ratio of the carbonized metal organic framework material to the hydrophilic polymer is 1:(0.1-1.2).
[0016] In some specific embodiments of the present invention, the thickness of the hydrophilic layer is 10 to 50 nm.
[0017] In some specific embodiments of the present invention, the thickness of the adsorption layer is ≥30 nm.
[0018] In some specific embodiments of the present invention, the thickness of the fixed layer is 30-200 nm.
[0019] The second aspect of the present invention provides a method for preparing a metal organic framework material composite film, comprising the following steps:
[0020] S1, taking a substrate, applying a preparation material of a hydrophilic layer on the surface of the substrate to form a hydrophilic layer;
[0021] S2, applying a first dispersion containing a carbonized metal organic framework material on the hydrophilic layer, and then drying to form an adsorption layer;
[0022] S3, applying a second dispersion containing a hydrophilic polymer on the adsorption layer, and then drying to form a fixed layer to obtain the metal organic framework material composite film;
[0023] The composition of the metal organic framework material composite film is as described in the first aspect of the present invention.
[0024] The preparation method according to the second aspect of the present invention has at least the following beneficial effects:
[0025] Since carbonized MOFs are easy to agglomerate and affect the uniform performance of membrane materials, making carbonized MOFs into a dispersion can improve its dispersibility. The adsorption layer can be obtained by a simple drying method. Then, a dispersion containing a hydrophilic polymer is applied to the adsorption layer. The hydrophilic polymer can form an intermolecular force with the hydrophilic layer to achieve good adhesion, thereby fixing the adsorption layer. The preparation process is simple, the equipment requirements are low, and the resulting composite membrane has good adsorption, stability and mechanical properties.
[0026] In some specific embodiments of the present invention, the solvent in the first dispersion is a first solvent, and the first solvent includes a volatile alcohol solvent.
[0027] In some specific embodiments of the present invention, the concentration of the carbonized metal organic framework material in the first dispersion is 20-100 mg / mL.
[0028] In some specific embodiments of the present invention, the solvent in the second dispersion is a second solvent, and the second solvent includes water, a volatile alcohol solvent or a combination thereof.
[0029] In some specific embodiments of the present invention, the concentration of the hydrophilic polymer in the second dispersion is 1-8 wt %.
[0030] In some specific embodiments of the present invention, in step S2, the carbonized metal organic framework material is obtained by carbonizing a metal organic framework material.
[0031] In some specific embodiments of the present invention, the temperature of the carbonization treatment is 500-1200°C.
[0032] In some specific embodiments of the present invention, the heating rate of the carbonization treatment is 1 to 10° C. / min.
[0033] In some specific embodiments of the present invention, the carbonization treatment time is 0.5 to 5 hours.
[0034] In some specific embodiments of the present invention, in step S2, the number of times of applying the first dispersion and then drying is 1 to 10 times.
[0035] In some specific embodiments of the present invention, in steps S2 to S3, the drying temperature is independently 40 to 100°C.
[0036] In some specific embodiments of the present invention, in steps S1 to S3, the application methods are independently selected from manual coating, electrostatic spraying or a combination thereof.
[0037] The third aspect of the present invention provides an application of the metal organic framework material composite membrane as described in the first aspect of the present invention, or the metal organic framework material composite membrane prepared by the preparation method described in the second aspect of the present invention in gas adsorption enrichment.
[0038] The application according to the third aspect of the present invention has at least the following beneficial effects:
[0039] The metal organic framework material composite membrane of the present invention has good adsorption performance, especially has good adsorption effect on gas, can realize gas adsorption enrichment, and the membrane material has high density, good mechanical properties, different layer structures are not easy to fall off and peel off, the overall adhesion of the material is strong, the uniformity is good, and the thickness is controllable. The composite membrane is used for gas adsorption enrichment, which can not only achieve good gas adsorption enrichment effect, but also has good mechanical properties and long service life.
[0040] In some specific embodiments of the present invention, the gas comprises an inert gas; in some more specific embodiments of the present invention, the gas comprises krypton and / or xenon.
[0041] The adsorption layer in the composite membrane material of the present invention contains carbonized MOFs material. The carbonized MOFs material has a specific pore structure and pore size, has a good adsorption effect on inert gases, especially krypton and / or xenon, and can be used for adsorption and enrichment of krypton and / or xenon.
[0042] The fourth aspect of the present invention provides a method for adsorption and enrichment of krypton and / or xenon, using the metal-organic framework material composite membrane described in the first aspect of the present invention, or the metal-organic framework material composite membrane prepared by the preparation method described in the second aspect of the present invention as an adsorbent, adsorbing a mixed gas containing krypton and / or xenon to achieve enrichment of krypton and / or xenon.
[0043] The adsorption enrichment method according to the fourth aspect of the present invention has at least the following beneficial effects:
[0044] The metal organic framework material composite membrane of the present invention has a good adsorption and enrichment effect on krypton and / or xenon. It can be used as an adsorbent to remove krypton and / or xenon in the mixed gas, thereby achieving effective adsorption and enrichment of krypton and / or xenon in the mixed gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is an optical microscope picture of the composite membrane material of Experimental Example 1.
[0046] Figure 2 This is an optical microscope picture of the composite membrane material of Experimental Comparative Example 1.
[0047] Figure 3 This is a SEM image of the cross section of the gelatin layer of Test Example 1.
[0048] Figure 4 These are the adsorption performance curves of krypton gas for CZIF-650, CZIF-800, CZIF-950 and uncarbonized ZIF-8.
[0049] Figure 5 These are the adsorption performance curves of xenon for CZIF-650, CZIF-800, CZIF-950 and uncarbonized ZIF-8.
[0050] Figure 6 This is a graph showing the adsorption performance of krypton and xenon before and after carbonized ZIF-8 is mixed with gelatin.
[0051] Figure 7 This is a flow chart for preparing the metal organic framework material composite membrane of Example 1.
[0052] Figure 8 This is the SEM image of the metal organic framework material composite film of Example 2.
[0053] Fig. 9 This is the SEM image of the metal organic framework material composite film of Example 3.
[0054] Fig.10 The graphs are the adsorption performance curves of krypton gas by the metal organic framework composite films and the PET substrate materials of Examples 2 to 3.
[0055] Fig.11 The graphs are the adsorption performance curves of the metal organic framework composite films and the PET substrate materials of Examples 2 to 3 for xenon. DETAILED DESCRIPTION
[0056] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0057] The first aspect of an embodiment of the present invention provides a metal-organic framework material composite membrane, comprising a substrate, a hydrophilic layer, an adsorption layer and a fixed layer arranged in sequence; the fixed layer is coated on the surface of the adsorption layer and connected to the hydrophilic layer; the adsorption layer contains a carbonized metal-organic framework material, and the fixed layer contains a hydrophilic polymer; the hydrophilic polymer includes at least one of gelatin, hyaluronic acid, chitosan, hyaluronic acid, polyethylene glycol, polyacrylic acid and its derivatives, polyvinyl alcohol, polyethylene oxide, polyacrylamide, polyhydroxyethyl methacrylate, polyacrylic acid or polymethacrylic acid.
[0058] In the embodiment of the present invention, a hydrophilic layer is firstly provided on the surface of the substrate to improve the hydrophilicity and adhesion of the substrate surface, which is beneficial to the attachment of the subsequent adsorption layer and the fixed layer. Due to the provision of the hydrophilic layer, the composite membrane can adopt substrates of various properties, and the requirements for the membrane substrate are low; if the hydrophilic layer is not provided, the adsorption layer and the fixed layer are difficult to be evenly dispersed and attached to the substrate, and the hydrophilic polymer of the fixed layer is also easy to agglomerate due to uneven distribution, resulting in uneven performance of the membrane material and poor material stability; then, carbonized metal organic framework materials (MOFs) are used as the adsorption layer. Carbonized MOFs have rich mesoporous structures and high specific surface areas. As adsorption materials, The material is beneficial to improving the adsorption activity of the composite membrane; and a fixed layer is set on the surface of the adsorption layer. Due to the good adhesion between the hydrophilic polymer in the fixed layer and the hydrophilic layer, the fixed layer plays a role similar to a "seat belt", wrapping the adsorption layer in contact with the hydrophilic layer, and better fixing the adsorption layer firmly in the membrane material to form a composite membrane material containing carbonized MOFs; and the hydrophilic polymers used in the present invention have good hydrophilic properties, strong adhesion to the hydrophilic layer, and good air permeability and stability, and will not affect the adsorption performance of the adsorption layer. While fixing the carbonized MOFs particles in the adsorption layer, it does not affect the adsorption activity of the carbonized MOFs. Through the design of the composite membrane structure of the present invention, a MOFs composite membrane with good adsorption performance is simply and efficiently prepared, without the need to adopt complex processes such as press molding, and the preparation process is simple. The obtained composite membrane has good mechanical properties, good stability, and high density, and has good application prospects in the preparation of gas adsorption materials.
[0059] In some embodiments of the present invention, the carbonized metal organic framework material is in a granular form.
[0060] By setting the hydrophilic layer and the fixed layer of the present invention, the granular carbonized metal organic framework material can be made into a membrane material, thereby broadening the industrial application of the MOFs material and giving full play to the excellent adsorption performance of the MOFs material.
[0061] In some embodiments of the present invention, the hydrophilic polymer includes at least one of gelatin, hyaluronic acid, chitosan, hyaluronic acid, polyethylene glycol, poly(hydroxyethyl methacrylate), polyacrylic acid or polymethacrylic acid; in some specific embodiments of the present invention, the hydrophilic polymer includes at least one of gelatin, hyaluronic acid, chitosan, hyaluronic acid or polyethylene glycol; in some examples of the present invention, the hydrophilic polymer is selected from gelatin.
[0062] The hydrophilic polymer used in the present invention not only has good hydrophilic properties, but also has good air permeability and stability, and as a fixed layer, it will not affect the adsorption performance of the adsorption layer. In particular, compared with other hydrophilic polymers, gelatin has better air permeability and stability, and using gelatin as the hydrophilic polymer in the fixed layer can obtain a composite membrane material with better adsorption performance and stronger mechanical properties.
[0063] In some embodiments of the present invention, the raw material for preparing the hydrophilic layer includes at least one of polyacrylic acid, methanol, ethanol or propanol; in some specific embodiments of the present invention, the raw material for preparing the hydrophilic layer includes polyacrylic acid, ethanol or a combination thereof.
[0064] The hydrophilic layer is prepared on the surface of the substrate using the above-mentioned compound with good hydrophilicity, which is beneficial to improving the hydrophilicity of the substrate surface and improving the adhesion between the substrate and the adsorption layer.
[0065] In some embodiments of the present invention, the material of the substrate includes at least one of polyethylene terephthalate (PET), a silicon plate, an aluminum foil or a plastic plate.
[0066] The material of the substrate can be selected according to actual needs or operating conditions, and the present invention does not make any specific limitation.
[0067] In some embodiments of the present invention, the mass ratio of the carbide metal organic framework material to the hydrophilic polymer is 1: (0.1-1.2); in some specific embodiments of the present invention, the mass ratio of the carbide metal organic framework material to the hydrophilic polymer is 1: (0.3-1); in some examples of the present invention, the mass ratio of the carbide metal organic framework material to the hydrophilic polymer is 1: (0.5-0.8); Non-limiting specific examples are 1: 0.55, 1: 0.6, 1: 0.65, 1: 0.7 or 1: 0.75.
[0068] In some embodiments of the present invention, the thickness of the hydrophilic layer is 10-50 nm; in some specific embodiments of the present invention, the thickness of the hydrophilic layer is 15-45 nm; in some examples of the present invention, the thickness of the hydrophilic layer is 20-40 nm. Non-limiting specific examples include 22 nm, 25 nm, 28 nm, 30 nm, 32 nm, 35 nm or 38 nm.
[0069] In some embodiments of the present invention, the thickness of the adsorption layer is ≥30 nm; in some specific embodiments of the present invention, the thickness of the adsorption layer is 30-20000 nm; in some examples of the present invention, the thickness of the adsorption layer is 100-15000 nm. Non-limiting specific examples include 200 nm, 400 nm, 800 nm, 1000 nm, 2000 nm, 5000 nm, 8000 nm, 10000 nm or 12000 nm.
[0070] The thickness of the adsorption layer can be set according to actual needs, such as by adding more carbonized metal organic framework materials, so as to achieve controllable thickness of the composite membrane and ensure that the composite membrane is uniform, easy to prepare and suitable for industrial production needs.
[0071] In some embodiments of the present invention, the thickness of the fixed layer is 30-200 nm; in some specific embodiments of the present invention, the thickness of the fixed layer is 50-180 nm; in some examples of the present invention, the thickness of the fixed layer is 80-150 nm. Non-limiting specific examples are 90 nm, 100 nm, 110 nm, 120 nm, 130 nm or 140 nm.
[0072] The fixed layer is provided to fix the adsorption layer and cannot affect the adsorption performance of the adsorption layer. Therefore, a certain air permeability is required. Keeping its thickness within a certain range can achieve good air permeability and stability of the composite membrane.
[0073] A second aspect of an embodiment of the present invention provides a method for preparing a metal organic framework material composite film according to the first aspect of the present invention, comprising the following steps:
[0074] S1, taking a substrate, applying a preparation material of a hydrophilic layer on the surface of the substrate to form a hydrophilic layer;
[0075] S2, applying a first dispersion containing a carbonized metal organic framework material on the hydrophilic layer, and then drying to form an adsorption layer;
[0076] S3, applying a second dispersion containing a hydrophilic polymer on the adsorption layer, and then drying to form a fixed layer to obtain the metal organic framework material composite film;
[0077] The composition of the metal organic framework material composite film is as described in the first aspect of the embodiment of the present invention.
[0078] Since carbonized MOFs are easy to agglomerate and affect the uniform performance of membrane materials, making carbonized MOFs into a dispersion can improve its dispersibility. The adsorption layer can be obtained by a simple drying method. Then, a dispersion containing a hydrophilic polymer is applied to the adsorption layer. The hydrophilic polymer can form an intermolecular force with the hydrophilic layer to achieve good adhesion, thereby fixing the adsorption layer. The preparation process is simple, the equipment requirements are low, and the resulting composite membrane has good adsorption, stability and mechanical properties.
[0079] In some embodiments of the present invention, the solvent in the first dispersion is a first solvent, and the first solvent includes a volatile alcohol solvent; in some specific embodiments of the present invention, the first solvent includes at least one of methanol, ethanol, isopropanol, butanol or pentanol; in some specific embodiments of the present invention, the first solvent includes methanol, ethanol or a combination thereof; in some examples of the present invention, the first solvent is selected from ethanol.
[0080] Using volatile alcohol solvents as the first solvent can achieve a good dispersion effect of carbonized MOFs in the first solvent, and the alcohol solvents have good affinity with the hydrophilic layer, which is beneficial to promote the uniform distribution of carbonized MOFs on the hydrophilic layer, thereby obtaining a composite membrane with uniform thickness, uniform performance, and stable adsorption performance. Volatile alcohol solvents have good volatility and fast drying speed, which is beneficial to improving the preparation efficiency of the composite membrane.
[0081] In some embodiments of the present invention, the concentration of the carbide metal organic framework material in the first dispersion is 20-100 mg / mL; in some specific embodiments of the present invention, the concentration of the carbide metal organic framework material in the first dispersion is 30-80 mg / mL; in some examples of the present invention, the concentration of the carbide metal organic framework material in the first dispersion is 40-70 mg / mL. Non-limiting specific examples are 45 mg / mL, 50 mg / mL, 55 mg / mL, 60 mg / mL or 65 mg / mL.
[0082] In some embodiments of the present invention, the carbonized metal organic framework material is further ground before preparing the first dispersion.
[0083] By grinding, the agglomeration of the carbonized metal organic framework material in the dispersion can be prevented, thereby avoiding affecting the uniform dispersion of the material in the dispersion.
[0084] In some embodiments of the present invention, the time for grinding the carbide metal organic framework material is 5 to 50 minutes; in some specific embodiments of the present invention, the time for grinding the carbide metal organic framework material is 10 to 40 minutes; in some examples of the present invention, the time for grinding the carbide metal organic framework material is 10 to 30 minutes; non-limiting specific examples are 15 minutes, 18 minutes, 20 minutes, 25 minutes or 28 minutes.
[0085] In some embodiments of the present invention, the solvent in the second dispersion is a second solvent, and the second solvent includes water, a volatile alcohol solvent or a combination thereof; in some specific embodiments of the present invention, the second solvent includes water and a volatile alcohol solvent; in some examples of the present invention, the second solvent includes water, and at least one of methanol, ethanol, isopropanol, butanol or pentanol; in some examples of the present invention, the second solvent includes water and ethanol.
[0086] The hydrophilic polymer in the embodiment of the present invention has good solubility in water. Using water as a solvent can obtain a second dispersion with better dissolution effect. Volatile alcohol solvents have good volatility and fast drying speed, which is beneficial to improving the preparation efficiency of the composite film.
[0087] In some embodiments of the present invention, the second solvent is selected from a mixed solution of water and a volatile alcohol solvent, and the volume ratio of water to the volatile alcohol solvent is 1: (1-10); in some specific embodiments of the present invention, the volume ratio of water to the volatile alcohol solvent is 1: (1.5-8); in some examples of the present invention, the volume ratio of water to the volatile alcohol solvent is 1: (2-5). Non-limiting specific examples are 1:2.5, 1:3, 1:3.5, 1:4 or 1:4.5.
[0088] By adjusting the usage ratio of water and volatile alcohol solvent, the dissolution stability and volatility of the second dispersion, as well as the affinity and adhesion to the hydrophilic layer can be adjusted, thereby obtaining a composite membrane material with better comprehensive performance.
[0089] In some embodiments of the present invention, the second solvent is selected from a mixed solution of water and ethanol, and the volume ratio of water to ethanol is 1: (1-10); in some specific embodiments of the present invention, the volume ratio of water to ethanol in the second solvent is 1: (1.5-8); in some examples of the present invention, the volume ratio of water to ethanol in the second solvent is 1: (2-5). Non-limiting specific examples are 1:2.5, 1:3, 1:3.5, 1:4 or 1:4.5.
[0090] In some embodiments of the present invention, the concentration of the hydrophilic polymer in the second dispersion is 1-8 wt %; in some specific embodiments of the present invention, the concentration of the hydrophilic polymer in the second dispersion is 1.5-6 wt %; in some examples of the present invention, the concentration of the hydrophilic polymer in the second dispersion is 2-4 wt %. Non-limiting specific examples include 2.2 wt %, 2.5 wt %, 2.8 wt %, 3 wt %, 3.2 wt %, 3.5 wt % or 3.8 wt %.
[0091] In some embodiments of the present invention, in step S2, the carbonized metal organic framework material is obtained by carbonizing the metal organic framework material.
[0092] By carbonizing MOFs, the material structure of MOFs can be changed to form carbonized MOFs with a loose porous structure and a large specific surface area, thereby greatly increasing the adsorption sites of the material and giving the material better adsorption properties.
[0093] In some embodiments of the present invention, the carbonization treatment is carried out in a protective gas atmosphere; in some specific embodiments of the present invention, the protective gas includes at least one of nitrogen, argon or helium; in some examples of the present invention, the protective gas is selected from nitrogen or argon.
[0094] In some embodiments of the present invention, the temperature of the carbonization treatment is 500-1200° C.; in some specific embodiments of the present invention, the temperature of the carbonization treatment is 600-1100° C.; in some examples of the present invention, the temperature of the carbonization treatment is 650-1000° C. Non-limiting specific examples are 700° C., 750° C., 800° C., 850° C., 900° C. or 950° C.
[0095] The temperature of the carbonization treatment will affect the carbonization degree of MOFs and the adsorption performance of the material. Within the temperature range of the carbonization treatment of the present invention, a composite membrane material with good adsorption effect can be obtained.
[0096] In some embodiments of the present invention, the heating rate of the carbonization treatment is 1 to 10°C / min; in some specific embodiments of the present invention, the heating rate of the carbonization treatment is 2 to 8°C / min; in some examples of the present invention, the heating rate of the carbonization treatment is 3 to 7°C / min. Non-limiting specific examples include 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, or 6.5°C / min.
[0097] In some embodiments of the present invention, the carbonization time is 0.5 to 5 hours; in some specific embodiments of the present invention, the carbonization time is 0.8 to 4 hours; in some examples of the present invention, the carbonization time is 1 to 3 hours. Non-limiting specific examples include 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, 2.2 hours, 2.5 hours or 2.8 hours.
[0098] In some embodiments of the present invention, the metal organic framework material includes at least one of IRMOF material, ZIF material, CPL material, MIL material, PCN material or UiO material; in some specific embodiments of the present invention, the metal organic framework material includes at least one of ZIF material, MIL material or UiO material; in some examples of the present invention, the metal organic framework material is selected from ZIF material.
[0099] In some embodiments of the present invention, the ZIF material includes at least one of ZIF-8, ZIF-67, ZIF-7, ZIF-9 or ZIF-100; in some specific embodiments of the present invention, the ZIF material includes at least one of ZIF-8, ZIF-67 or ZIF-7; in some examples of the present invention, the ZIF material is selected from ZIF-8.
[0100] In some embodiments of the present invention, in step S2, the steps of applying the first dispersion and then drying can be repeated; in some specific embodiments of the present invention, in step S2, the number of times of applying the first dispersion and then drying is 1 to 10 times; non-limiting specific examples are 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times or 9 times.
[0101] The thickness of the composite film can be adjusted by adjusting the number of times the first dispersion is applied in step S2. Therefore, the thickness of the composite film of the present invention is controllable and has good uniformity. The thickness adjustment method is simple and can meet the needs of different application scenarios.
[0102] In some embodiments of the present invention, in step S2, the drying temperature is 40-100°C; in some embodiments of the present invention, in step S2, the drying temperature is 50-90°C; in some embodiments of the present invention, in step S2, the drying temperature is 60-80°C; non-limiting specific examples are 65°C, 68°C, 70°C, 75°C or 78°C.
[0103] In some embodiments of the present invention, in step S3, the drying temperature is 40-100°C; in some embodiments of the present invention, in step S3, the drying temperature is 50-90°C; in some embodiments of the present invention, in step S3, the drying temperature is 60-80°C; non-limiting specific examples are 65°C, 68°C, 70°C, 75°C or 78°C.
[0104] In some embodiments of the present invention, in step S1, the applying method is selected from manual coating, electrostatic spraying or a combination thereof. Specifically, the applying in step S1 refers to applying the raw materials for preparing the hydrophilic layer.
[0105] In some embodiments of the present invention, in step S2, the applying method is selected from manual coating, electrostatic spraying or a combination thereof. Specifically, the applying in step S2 refers to applying a first dispersion containing a carbonized metal organic framework material.
[0106] In some embodiments of the present invention, in step S3, the applying method is selected from manual coating, electrostatic spraying or a combination thereof. Specifically, the applying in step S3 refers to applying the second dispersion containing the hydrophilic polymer.
[0107] In some embodiments of the present invention, the voltage of electrostatic spraying is 5-10 kV; non-limiting examples are 6 kV, 7 kV, 8 kV or 9 kV.
[0108] In some embodiments of the present invention, the speed of the electrostatic spraying nozzle is 20-40 mm / min; non-limiting examples are 25 mm / min, 30 mm / min or 35 mm / min.
[0109] In some embodiments of the present invention, the rotation speed of the electrostatic spraying drum is 40-60 rpm; non-limiting examples are 45 rpm, 50 rpm or 55 rpm.
[0110] In some embodiments of the present invention, the injection speed of electrostatic spraying is 4-8 mL / h; non-limiting examples are 5 mL / h, 6 mL / h or 7 mL / h.
[0111] The third aspect of the embodiments of the present invention provides an application of the metal-organic framework material composite membrane as in the first aspect of the embodiments of the present invention, or the metal-organic framework material composite membrane prepared by the preparation method of the second aspect of the embodiments of the present invention in gas adsorption enrichment.
[0112] The metal-organic framework material composite membrane of the embodiment of the present invention has good adsorption performance, especially good adsorption effect on gas, and can achieve gas adsorption enrichment. The membrane material has high density, good mechanical properties, and different layer structures are not easy to fall off and peel off. The overall adhesion of the material is strong, the uniformity is good, and the thickness is controllable. Using the composite membrane for gas adsorption enrichment can not only achieve good gas adsorption enrichment effect, but also the membrane has good mechanical properties and a long service life.
[0113] In some embodiments of the present invention, the gas includes an inert gas; in some specific embodiments of the present invention, the gas includes krypton and / or xenon.
[0114] The adsorption layer in the composite membrane material of the present invention contains carbonized MOFs material. The carbonized MOFs material has a specific pore structure and pore size, has a good adsorption effect on inert gases, especially krypton and / or xenon, and can be used for adsorption and enrichment of krypton and / or xenon.
[0115] The fourth aspect of the embodiments of the present invention provides a method for adsorption and enrichment of krypton and / or xenon, using the metal-organic framework material composite membrane of the first aspect of the embodiments of the present invention, or the metal-organic framework material composite membrane prepared by the preparation method of the second aspect of the embodiments of the present invention as an adsorbent, to adsorb a mixed gas containing krypton and / or xenon, thereby achieving enrichment of krypton and / or xenon.
[0116] The metal organic framework material composite membrane of the present invention has a good adsorption and enrichment effect on krypton and / or xenon. It can be used as an adsorbent to remove krypton and / or xenon in the mixed gas, thereby achieving effective adsorption and enrichment of krypton and / or xenon in the mixed gas.
[0117] The present invention is further described below in conjunction with specific test examples, embodiments and comparative examples.
[0118] In the following test examples, embodiments and comparative examples, the performance tests were carried out as follows:
[0119] 1) Morphology test: The samples were observed using a scanning electron microscope (SEM).
[0120] 2) Krypton and xenon adsorption performance test: At room temperature (20-30°C), the samples of the test examples, embodiments and comparative examples were used as adsorbents to conduct adsorption tests on pure krypton gas and pure xenon gas, respectively. The test instrument was a fully automatic BET specific surface (area) analysis tester.
[0121] Test Example 1
[0122] A composite membrane material, comprising the following preparation method:
[0123] Take a silicon wafer (pink) as a substrate, spray ethanol evenly on the substrate to make the surface of the substrate hydrophilic to obtain a hydrophilic layer; then spray 4wt% gelatin solution evenly on the surface of the material. The gelatin solution is prepared by dissolving gelatin in a mixed solution of water and ethanol (the volume ratio of water to ethanol is 1:3). After drying, a gelatin layer is formed to obtain the composite membrane material of this example.
[0124] Test Example 2
[0125] A composite membrane material, which differs from Experimental Example 1 in that a polyacrylic acid aqueous solution with a concentration of 2wt% is evenly sprayed on a substrate to obtain a hydrophilic layer, and other preparation materials and preparation methods are the same as those of Experimental Example 1.
[0126] Comparative Example 1
[0127] A composite membrane material, comprising the following preparation method:
[0128] A silicon wafer (pink) is taken as a substrate, and ethanol is sprayed unevenly, that is, part of the surface of the substrate is sprayed with ethanol, while the other part of the surface is not sprayed with ethanol, so as to obtain a hydrophilic layer set on part of the surface of the substrate; then a 4wt% gelatin solution is evenly sprayed on the surface of the material, and the gelatin solution is prepared by dissolving gelatin in a mixed solution of water and ethanol (the volume ratio of water to ethanol is 1:3), so as to obtain the composite membrane material of this example.
[0129] The composite film materials of Test Examples 1 to 2 and Experimental Comparative Example 1 were observed under an optical microscope. Since the gelatin material was light yellow, it would be difficult to observe it under an optical microscope if it formed a uniform film. Therefore, two marks were made in the composite film material of Test Example 1 for easy observation. Figure 1 This is an optical microscope image of the composite film material of Test Example 1. Only two artificial scratches are shown on the image. The thickness and color of the other parts are uniform, showing the pink color of the base. It can be seen that the uniform coating of ethanol in Test Example 1 is conducive to the uniform distribution of gelatin on the base, and a composite film material with uniform thickness and color is obtained. The results of Test Example 2 are similar to those of Test Example 1. The polyacrylic acid aqueous solution is used for uniform coating on the base, which is also conducive to obtaining a uniform composite film material.
[0130] Figure 2 This is an optical microscope picture of the composite membrane material of Experimental Example 1, showing uneven pink, green and yellow parts, wherein the pink part is the part on the substrate surface sprayed with ethanol, and a uniformly formed gelatin layer can be obtained, thus showing the pink color of the substrate; the green part and the yellow part are the parts on the substrate surface not sprayed with ethanol, and uneven gelatin agglomeration occurs in these parts, the green part is formed by slight agglomeration of gelatin, and the yellow part is formed by severe agglomeration of gelatin. It can be seen that the provision of an ethanol layer on the substrate surface is important for the uniform formation of the gelatin layer. If the ethanol layer is not sprayed, the gelatin solution is easily unevenly distributed, resulting in agglomeration, and it is difficult to form a composite membrane material with uniform performance.
[0131] Figure 3 This is the SEM image of the cross section of the gelatin layer of Experimental Example 1. It can be seen that the gelatin layer prepared by the method of Experimental Example 1 is thin and uniform, with a thickness of about 100 nm.
[0132] Test Example 3
[0133] In order to test the effects of carbonization treatment and carbonization temperature on the adsorption properties of carbonized ZIF-8 materials, ZIF-8 materials were carbonized at different carbonization temperatures (650°C, 800°C, 950°C). The specific steps are as follows: Grind the ZIF-8 powder and put it into a ceramic crucible, and carbonize it under Ar / N2 atmosphere. The tubular furnace heating process is as follows: Heat to 650°C, 800°C or 950°C at a heating rate of 5°C / min, keep warm for 2h, and then cool with the furnace temperature to obtain carbonized ZIF-8 materials, which are respectively recorded as CZIF-650, CZIF-800, and CZIF-950. The room temperature krypton and xenon adsorption properties of CZIF-650, CZIF-800, CZIF-950 and uncarbonized ZIF-8 were tested, and the results are as follows: Figure 4 and Figure 5 shown.
[0134] Figure 4 The adsorption performance curves of CZIF-650, CZIF-800, CZIF-950 and uncarbonized ZIF-8 for krypton gas are shown in Figure 2. Figure 5 The adsorption performance curves of CZIF-650, CZIF-800, CZIF-950 and uncarbonized ZIF-8 for xenon. It can be seen that compared with the uncarbonized ZIF-8 material, the carbonized ZIF-8 material has a higher adsorption capacity for krypton and xenon, and has better adsorption performance. And within the carbonization temperature range of the present invention, the adsorption performance of the carbonized ZIF-8 material for krypton and xenon is proportional to the carbonization temperature, and the carbonized ZIF-8 material (CZIF-950) obtained at a carbonization temperature of 950°C performs best.
[0135] Test Example 4
[0136] In order to test the effect of gelatin on the adsorption performance of carbonized ZIF-8, carbonized ZIF-8 (CZIF-950) and gelatin were mixed in a mass ratio of 3:2 and then the krypton and xenon adsorption performance at room temperature was tested. The results were compared with the carbonized ZIF-8 of the same mass that was not mixed with gelatin. Figure 6 shown.
[0137] Figure 6 The graph shows the adsorption performance of krypton and xenon by carbonized ZIF-8 before and after mixing with gelatin. Kr-gelatin shows the adsorption performance of krypton by carbonized ZIF-8 mixed with gelatin, Xe-gelatin shows the adsorption performance of xenon by carbonized ZIF-8 mixed with gelatin, Kr shows the adsorption performance of krypton by carbonized ZIF-8 alone, and Xe shows the adsorption performance of xenon by carbonized ZIF-8 alone. Figure 6It can be seen that compared with the carbonized ZIF-8 material alone, the composite material obtained by mixing the carbonized ZIF-8 material with gelatin still has good krypton-xenon adsorption performance, indicating that gelatin has good air permeability and its wrapping on the surface of the carbonized ZIF-8 material has little effect on the adsorption performance of the obtained composite material.
[0138] Example 1
[0139] A metal organic framework material composite membrane comprises a substrate, a hydrophilic layer, an adsorption layer and a fixed layer which are stacked in sequence; the substrate material is PET, the hydrophilic layer is an ethanol layer, the adsorption layer is a carbonized ZIF-8 layer, and the fixed layer is a gelatin layer; the fixed layer is coated on the surface of the adsorption layer and connected to the hydrophilic layer.
[0140] The metal organic framework composite membrane in this example was prepared by manual coating. The preparation process is shown in the following figure. Figure 7 As shown, the specific steps include:
[0141] 1) Preparation of carbonized ZIF-8 material: Grind the ZIF-8 powder and put it into a ceramic crucible for carbonization in an Ar / N2 atmosphere. The heating process of the tubular furnace is as follows: heat to 950°C at a heating rate of 5°C / min, keep warm for 2 hours, and then cool with the furnace temperature to obtain the carbonized ZIF-8 material. In order to prevent the carbonized ZIF-8 material from agglomerating and affecting the dispersion of the subsequent material in the ethanol / methanol solution, grind the carbonized ZIF-8 material using a ball mill or mortar for 30 minutes.
[0142] 2) Preparation of a hydrophilic layer: Take a substrate, spray ethanol evenly on the substrate, dry the substrate at 80° C. to obtain a hydrophilic layer, and prepare a hydrophilic layer to improve the hydrophilicity of the substrate surface and increase adhesion.
[0143] 3) Preparation of carbonized ZIF-8 material layer: 400 mg of ground carbonized ZIF-8 material was dispersed in 10 mL of ethanol solution, and ultrasonic stirring was performed for 2 h in advance. The upper solution was taken to obtain a carbonized ZIF-8 material dispersion, wherein the concentration of the carbonized ZIF-8 material was 40 mg / mL. A model air pump airbrush coloring instrument of Ningbo Haosheng Pneumatic Machinery Co., Ltd. was used, and the carbonized ZIF-8 material dispersion was placed in the airbrush coloring instrument, and the carbonized ZIF-8 material dispersion was manually coated on the substrate material, and the substrate was dried at 80°C.
[0144] 4) Spraying the fixed layer: dissolving gelatin in a mixed solution of water and ethanol, with a volume ratio of water to ethanol of 1:3, to obtain a 2wt% gelatin solution. Spraying the gelatin solution onto the dried carbonized ZIF-8 material layer according to the spraying method in 3), after drying, the gelatin fixed layer is coated on the surface of the carbonized ZIF-8 material layer and contacts the hydrophilic layer, to obtain the metal organic framework material composite film.
[0145] Example 2
[0146] A metal organic framework material composite membrane comprises a substrate, a hydrophilic layer, an adsorption layer and a fixed layer which are stacked in sequence; the substrate material is PET, the hydrophilic layer is a polyacrylic acid layer, the adsorption layer is a carbonized ZIF-8 layer, and the fixed layer is a gelatin layer; the fixed layer is coated on the surface of the adsorption layer and connected to the hydrophilic layer.
[0147] The metal organic framework material composite film of this example is prepared by electrostatic spraying, which specifically includes the following steps:
[0148] 1) Preparation of carbonized ZIF-8 material: Grind the ZIF-8 powder and put it into a ceramic crucible for carbonization in an Ar / N2 atmosphere. The heating process of the tubular furnace is as follows: heat to 950°C at a heating rate of 5°C / min, keep warm for 2 hours, and then cool with the furnace temperature to obtain the carbonized ZIF-8 material. In order to prevent the carbonized ZIF-8 material from agglomerating and affecting the dispersion of the subsequent material in the ethanol / methanol solution, grind the carbonized ZIF-8 material using a ball mill or mortar for 30 minutes.
[0149] 2) Preparation of a hydrophilic layer: Take a substrate and evenly spray a 2 wt % polyacrylic acid aqueous solution on the substrate to obtain a hydrophilic layer, so as to improve the hydrophilicity of the substrate surface and increase the adhesion.
[0150] 3) Preparation of carbonized ZIF-8 material layer: Disperse 400 mg of ground carbonized ZIF-8 material into 10 mL of ethanol solution, pre-ultrasonicate for 2 h, take the upper solution, and obtain a carbonized ZIF-8 material dispersion, wherein the concentration of the carbonized ZIF-8 material is 40 mg / mL. Take an electrostatic sprayer, place the substrate material prepared with a hydrophilic layer on the roller of the electrostatic sprayer, and evenly spray the carbonized ZIF-8 material dispersion on the hydrophilic layer by electrostatic spraying. The spraying time is 1 h. The voltage of the process is set to 7 kV, the nozzle speed is set to 30 mm / min, the drum speed is 50 rpm, and the injection speed is 6 mL / h. Dry the substrate at 80 °C.
[0151] 4) Spraying fixed layer: Gelatin is dissolved in a mixed solution of water and ethanol, the volume ratio of water to ethanol is 1:3, and a 3wt% gelatin solution is obtained. The above gelatin solution is sprayed onto the dried carbonized ZIF-8 material layer according to the electrostatic spraying method and conditions in 3), and the spraying time is 15min. After drying, the gelatin fixed layer is coated on the surface of the carbonized ZIF-8 material layer and contacts the hydrophilic layer, and the metal organic framework material composite film is obtained. The composite film obtained in this example is recorded as CZIF-950-1x.
[0152] Example 3
[0153] A metal organic framework material composite membrane, which is different from Example 2 in that in the preparation method of this example, step 3) is repeated to spray the carbonized ZIF-8 material dispersion liquid 5 times, and the other preparation raw materials and preparation methods are the same as those of Example 2. The composite membrane obtained in this example is recorded as CZIF-950-5x.
[0154] Comparative Example 1
[0155] A metal organic framework material composite membrane is different from Example 2 in that no fixed layer is provided in this example, and other preparation raw materials and preparation methods are the same as those in Example 2.
[0156] Figure 8 The SEM images of the metal organic framework composite film of Example 2, wherein (A) and (B) are planar SEM images at different magnifications, and (C) is a cross-sectional SEM image; Fig. 9 The SEM images of the metal organic framework composite film of Example 3, wherein (A) and (B) are planar SEM images at different magnifications, and (C) is a cross-sectional SEM image. Figures 8-9 It can be seen that the metal organic framework composite membrane has a rich pore structure and good density. Figures 8-9 It can be seen that CZIF-950-5x has a thicker film thickness than CZIF-950-1x. By repeating the step 3) of spraying the carbonized ZIF-8 material dispersion, composite membrane materials of different thicknesses can be obtained, thereby achieving the characteristic of controllable membrane thickness, and the thickness of the membrane can be adjusted according to actual needs, and the adjustment method is simple and easy. Since the adsorption layer is the main adsorption layer of the composite membrane material, a larger adsorption layer thickness is conducive to obtaining a material with better adsorption performance.
[0157] Fig.10 is the adsorption performance curve of krypton gas by the metal organic framework material composite film and the PET substrate material of Examples 2 to 3, Fig.11 The adsorption performance curves of the metal organic framework material composite film and the PET substrate material for xenon in Examples 2 to 3 show that providing an adsorption layer on the PET substrate material can improve the material's adsorption performance for krypton and xenon, and that adjusting the thickness of the adsorption layer can effectively improve the composite film's adsorption performance for krypton and xenon.
[0158] From the perspective of mechanical properties and stability, Comparative Example 1 did not fix the ZIF-8 material, and the carbonized ZIF-8 material was very easy to fall off, with poor mechanical properties and stability and a short service life, which seriously affected its industrial application. However, Examples 1 to 3 used a gelatin layer and a hydrophilic layer to fix the carbonized ZIF-8 material, and the obtained composite membrane had good mechanical properties, high adhesion, strong stability, long service life, and good adsorption properties, and had good application prospects in industry.
[0159] From the above test examples, embodiments and comparative examples, it can be seen that the metal organic framework material composite film obtained by the method of the present invention has high density, good mechanical properties, high adhesion, uniform film structure, thin and controllable thickness, and importantly, has good gas adsorption performance, especially high adsorption capacity for Kr and Xe, and has a wide range of applications in the adsorption enrichment of krypton and / or xenon. The base material of the present invention can be flexibly switched and selected according to the actual industrial application scenario, and the size of the film can be tailored according to actual needs, the area size is controllable, and the thickness can be adjusted by regulating the thickness of the adsorption layer. The composite film of the present invention can be applied to various different industrial production needs, has low requirements for equipment, and has a simple preparation process and is easy to implement.
[0160] In the metal organic framework material composite membrane of the embodiment of the present invention, its adsorption layer contains carbonized MOFs material. Compared with the uncarbonized MOFs material, the carbonized MOFs material has a specific pore structure and pore size, and has a good adsorption effect on krypton and / or xenon. Therefore, the metal organic framework material composite membrane of the embodiment of the present invention can be used for adsorption and enrichment of krypton and / or xenon. Based on the good adsorption capacity of the composite membrane material in the embodiment of the present invention for Kr and Xe, the composite membrane material in the embodiment of the present invention is used as an adsorbent to remove krypton and / or xenon from the mixed gas, thereby achieving effective adsorption and enrichment of krypton and / or xenon in the mixed gas.
[0161] In summary, the present invention adopts a carbide metal organic framework material as the adsorption layer. The material has a rich mesoporous structure and a high specific surface area. As an adsorption material, it is beneficial to improve the adsorption activity of the composite membrane. By cooperating with the hydrophilic layer and the fixed layer and utilizing the good adhesion between the two, the adsorption layer can be firmly fixed in the membrane material to form a carbide metal organic framework material composite membrane with good adsorption performance, high mechanical properties, good stability and high density. The preparation process is simple and the equipment requirements are low. The composite membrane of the present invention has good application prospects in gas adsorption and enrichment, especially in the adsorption and enrichment of krypton and / or xenon.
Claims
1. A metal organic framework composite film, characterized in that: The invention comprises a substrate, a hydrophilic layer, an adsorption layer and a fixed layer which are arranged in sequence; the fixed layer is coated on the surface of the adsorption layer and connected to the hydrophilic layer; the adsorption layer contains a carbonized metal organic framework material, and the fixed layer contains a hydrophilic polymer; the hydrophilic polymer comprises at least one of gelatin, hyaluronic acid, chitosan, hyaluronic acid, polyethylene glycol, polyacrylic acid and its derivatives, polyvinyl alcohol, polyethylene oxide, polyacrylamide, polyhydroxyethyl methacrylate, polyacrylic acid or polymethacrylic acid.
2. The metal organic framework composite membrane according to claim 1, wherein the raw material for preparing the hydrophilic layer comprises at least one of polyacrylic acid, methanol, ethanol or propanol; And / or, the material of the substrate includes at least one of polyethylene terephthalate, silicon plate, aluminum foil or plastic plate.
3. The metal organic framework composite film according to claim 1, characterized in that: The mass ratio of the carbonized metal organic framework material to the hydrophilic polymer is 1:(0.1-1.2).
4. The metal organic framework composite film according to any one of claims 1 to 3, characterized in that: The thickness of the hydrophilic layer is 10 to 50 nm; And / or, the thickness of the adsorption layer is ≥30 nm; And / or, the thickness of the fixed layer is 30-200 nm.
5. A method for preparing a metal organic framework composite film, characterized in that: The following steps are involved: S1, taking a substrate, applying a preparation material of a hydrophilic layer on the surface of the substrate to form a hydrophilic layer; S2, applying a first dispersion containing a carbonized metal organic framework material on the hydrophilic layer, and then drying to form an adsorption layer; S3, applying a second dispersion containing a hydrophilic polymer on the adsorption layer, and then drying to form a fixed layer to obtain the metal organic framework material composite film; The composition of the metal organic framework material composite film is as described in any one of claims 1 to 4.
6. The preparation method according to claim 5, characterized in that: The solvent in the first dispersion is a first solvent, and the first solvent includes a volatile alcohol solvent; and / or, the concentration of the carbonized metal organic framework material in the first dispersion is 20 to 100 mg / mL; and / or, the solvent in the second dispersion is a second solvent, and the second solvent includes water, a volatile alcohol solvent or a combination thereof; And / or, the concentration of the hydrophilic polymer in the second dispersion is 1 to 8 wt %.
7. The preparation method according to claim 5, characterized in that: In the step S2, the carbonized metal organic framework material is obtained by carbonizing a metal organic framework material; preferably, the temperature of the carbonization treatment is 500 to 1200°C; and / or the heating rate of the carbonization treatment is 1 to 10°C / min; and / or the time of the carbonization treatment is 0.5 to 5h.
8. The preparation method according to claim 5, characterized in that: In step S2, the number of times of applying the first dispersion and then drying is 1 to 10 times; And / or, in the steps S2 to S3, the drying temperature is independently 40 to 100° C.; And / or, in the steps S1 to S3, the application methods are independently selected from manual coating, electrostatic spraying or a combination thereof.
9. Use of the metal organic framework material composite membrane as described in any one of claims 1 to 4, or the metal organic framework material composite membrane prepared by the preparation method as described in any one of claims 5 to 8 in gas adsorption enrichment, wherein the gas preferably includes an inert gas.
10. A method for enriching krypton and / or xenon by adsorption, characterized in that: The metal organic framework material composite film described in any one of claims 1 to 4, or the metal organic framework material composite film prepared by the preparation method described in any one of claims 5 to 8 is used as an adsorbent to adsorb a mixed gas containing krypton and / or xenon to achieve the enrichment of krypton and / or xenon.
Citation Information
Patent Citations
Regular-structure adsorbing material preparation, adsorbing material and application
CN106807330A
Metal organic framework material for adsorption separation of xenon gas and krypton gas and preparation method and application thereof
CN108993417A
Metal-organic framework nano-sheet composite film, preparation method and application thereof
CN110270232A
Metal organic framework material ZIF composite membrane as well as preparation method and application thereof
CN118892747A
Metal-organic framework for collecting krypton or xenon, and apparatus for collecting krypton or xenon, comprising same
WO2023113273A1
Cited By
Metal organic framework material composite membrane, and preparation method therefor and use thereof
WO2026108635A1